2017
DOI: 10.1038/mp.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Diazepam actions in the VTA enhance social dominance and mitochondrial function in the nucleus accumbens by activation of dopamine D1 receptors

Abstract: Benzodiazepines can ameliorate social disturbances and increase social competition, particularly in high-anxious individuals. However, the neural circuits and mechanisms underlying benzodiazepines’ effects in social competition are not understood. Converging evidence points to the mesolimbic system as a potential site of action for at least some benzodiazepine-mediated effects. Furthermore, mitochondrial function in the nucleus accumbens (NAc) has been causally implicated in the link between anxiety and social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 60 publications
(77 reference statements)
9
109
0
1
Order By: Relevance
“…Further insights for a key role of mitochondrial function in specific brain regions in influencing complex social behaviors have been provided by a series of studies in rats relating anxiety with diminished social competitiveness (Hollis et al, 2015; van der Kooij et al, 2017), a phenomenon that has also been highlighted in humans (Goette et al, 2015). In rats, lower mitochondrial function in the nucleus accumbens was observed in high-anxious animals compared to their less anxious littermates, and was causally implicated in their low social competitiveness (Hollis et al, 2015).…”
Section: Mitochondrial Function In the Brain Influences Social Bementioning
confidence: 99%
See 1 more Smart Citation
“…Further insights for a key role of mitochondrial function in specific brain regions in influencing complex social behaviors have been provided by a series of studies in rats relating anxiety with diminished social competitiveness (Hollis et al, 2015; van der Kooij et al, 2017), a phenomenon that has also been highlighted in humans (Goette et al, 2015). In rats, lower mitochondrial function in the nucleus accumbens was observed in high-anxious animals compared to their less anxious littermates, and was causally implicated in their low social competitiveness (Hollis et al, 2015).…”
Section: Mitochondrial Function In the Brain Influences Social Bementioning
confidence: 99%
“…Conversely, intraaccumbal infusion of nicotinamide, an amide form of vitamin B3 known to enhance brain energy metabolism, prevented the development of a subordinate status in anxious rats (Hollis et al, 2015). Additionally, treatment with a low dose of the anxiolytic diazepam was effective to facilitate social dominance, ameliorating both the competitive disadvantage and low mitochondrial function in the nucleus accumbens displayed by high-anxious rats (van der Kooij et al, 2017). …”
Section: Mitochondrial Function In the Brain Influences Social Bementioning
confidence: 99%
“…In addition, low exploratory mice are more submissive in the resident/intruder test than high exploratory mice. Given the existing link between anxiety and social competition, future studies should address the potential contribution of anxiety trait for rank‐related susceptibility to stress.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…The neural energetic state of neurons and glial cells, however, also alters signaling potential of neural circuits and responds to signaling events. Several studies have demonstrated that neural energetic state, described as the activity of metabolic pathways, including glycolysis and oxidative phosphorylation, predicts the outcome of social interactions (Hollis et al, ; van der Kooij et al, ; Li‐Byarlay, Rittschof, Massey, Pittendrigh, & Robinson, ; Rittschof, Vekaria, Palmer, & Sullivan, ), and is regulated by social experience (Alaux et al, ; Chandrasekaran et al, ; Dong et al, ; Li‐Byarlay et al, ; Rittschof et al, ). These studies observe such relationships at the whole brain level as well as in behavior‐relevant brain regions.…”
Section: Introductionmentioning
confidence: 99%